High-quality low-cost DC power supply using a simple control method / Muhd Nurfaiz Baharuddin - Baharuddin, Muhd Nurfaiz (2009)
This project describes a high-quality low-cost DC power supply using a simple control method to compensate the pulsating supply current to become a continuous, sinusoidal and in-phase with the supply voltage with unity power factor.